Impact of iron deficiency anemia on the function of the immune system in children. Issue 47 (November 2016) - Hassan, Tamer Hasan; Badr, Mohamed Ahmed; Karam, Nehad Ahmed; Zkaria, Marwa; El Saadany, Hosam Fathy; Abdel Rahman, Doaa Mohamed; Shahbah, Doaa Abdallah; Al Morshedy, Salah Mohamed; Fathy, Manar; Esh, Asmaa Mohamed Hosni; Selim, Amal Mohamed
Abstract : Abstract: The importance of iron deficiency as a public health problem is based ultimately on the seriousness of its consequences on health. The most extensively investigated consequences of iron deficiency involve work performance and immune function. The significance of the effects on work performance is generally accepted. In contrast, data on the influence of iron deficiency on immune function are often perceived as being confusing and contradictory. We aimed to evaluate the effect of iron deficiency anemia on humoral, cellular, nonspecific immunity, and also the effect on the cytokines that are the key factors of many immunologic steps. Forty children with iron deficiency anemia and 20 age and sex-matched healthy children were included. All children were subjected to full medical history, thorough clinical examination, complete blood count, iron indices (serum iron, serum total iron-binding capacity, serum ferritin, and transferrin saturation), immunoglobulin assay (IgA, IgG, and IgM), interleukin (IL)-6 serum level, study of T-lymphocyte subsets, and evaluation of phagocytic function of macrophages and oxidative burst activity of neutrophils. Patients had significantly lower IgG levels, IL-6, phagocytic activity, and oxidative burst of neutrophils than controls, although there was no significant difference between patients and controls with regard to other immunoglobulins and CD4/CD8 ratio. There was significantly positive correlation between serum iron and IL-6 serum level. We concluded that humoral, nonspecific immunity (phagocytic activity and oxidative burst), and the IL-6 are influenced in patients with iron deficiency anemia. Study of these abnormalities after correction of iron deficiency is strongly needed.